Adenosine A2B Receptor: From Cell Biology to Human Diseases - Sun, Ying; Huang, Pingbo (Frontiers in Chemistry, 2016)
Extracellular adenosine is a ubiquitous signaling molecule that modulates a wide array of biological processes. Recently, significant advances have been made in our understanding of A2B adenosine receptor (A2BAR). In this review, we first summarize some of the general characteristics of A2BAR, and then we describe the multiple binding partners of the receptor, such as newly identified α-actinin-1 and p105, and discuss how these associated proteins could modulate A2BAR’s functions, including certain seemingly paradoxical functions of the receptor. Growing evidence indicates a critical role of A2BAR in cancer, renal disease, and diabetes, in addition to its importance in the regulation of vascular diseases and lung disease. Here, we also discuss the role of A2BAR in cancer, renal disease, and diabetes and the potential of the receptor as a target for treating these three diseases.